Pengaruh Strategi Diferensiasi terhadap Keunggulan Bersaing pada Hotel Sumber Alam Cipanas Garut - Andri M Nuroni (Fakultas Ekonomi Universitas Garut, 2017)
The purpose of this study was to determine the effect of differentiation strategies on competitive advantage at Hotel Sumber Alam Cipanas Garut. This research uses descriptive and verification methods. The respondents of this study were 67 respondents who were selected using simple random sampling technique. The analysis technique used in this research is validity and reliability testing, descriptive analysis, classical assumption test, simple linear regression, and hypothesis testing using SPSS. 20. The results showed that there was an effect of differentiation strategy on competitive advantage at Hotel Sumber Alam Cipanas Garut. The conclusion of this research is that the formulation of the problem can be answered by the research hypothesis. So it is suggested to other researchers to conduct research with other variables which the author does not examine but affects this research such as; motivation, work environment, organizational culture and others.